Empowering the affected: Informing community-based solutions through interviews with survivors of interpersonal firearm violence—Perspectives of survivors of firearm injuries. Issue 6 (June 2021) - Halimeh, Bachar N.; Hughes, Dorothy; Evans, Blake; Emberson, Julia; Turco, Lauren; Zakrison, Tanya L.; Winfield, Robert D.
Abstract : BACKGROUND: Firearm violence remains epidemic in the United States, with interpersonal gun violence leading to significant morbidity and mortality. Interpersonal violence has strong associations with social determinants of health, and community-specific solutions are needed to address root causes. We hypothesized that open-ended interviews with survivors of interpersonal firearm violence would identify themes in individual and community-level factors that contribute to ongoing violence. METHODS: Between July 2017 and November 2019, we performed a mixed-methods study in which qualitative and quantitative data were obtained from survivors of interpersonal firearm violence admitted to our urban level I trauma center. Qualitative data were obtained through semistructured, open-ended interviews with survivors. Quantitative data were obtained via survey responses provided to these same individuals. Qualitative and quantitative data were then used to triangulate and strengthen results. RESULTS: During the study period, 51 survivors were enrolled in the study. The most common cause of firearm violence reported by survivors was increased gang and drug activity (n = 40, 78%). The most common solution expressed was to reduce drug and gang lifestyle by offering jobs and educational opportunities to afflicted communities to improve opportunities (n = 35, 69%). Nearly half of the survivors (n = 23, 45%) believe that firearm violence should be dealt with by the affected community itself, and another group of survivors believe that it should be through partnership between the community and trauma centers (n = 19, 37%). CONCLUSION: Interviews with survivors of firearm violence at our urban level I trauma center suggest that drug and gang lifestyle perpetuate ongoing violence and that this would best be overcome by improving access to quality education and job opportunities. To address endemic firearm violence in their communities, trauma centers should identify opportunities to partner in developing programs that provide improved education, job access, and conflict mediation. LEVEL OF EVIDENCE: Prognostic and epidemiological, level I.